2018
DOI: 10.1002/prp2.441
|View full text |Cite
|
Sign up to set email alerts
|

Cellular density‐dependent increases in HIF‐1α compete with c‐Myc to down‐regulate human EP4 receptor promoter activity through Sp‐1‐binding region

Abstract: The up‐regulated expression of E‐type prostanoid (EP) 4 receptors has been implicated in carcinogenesis; however, the expression of EP4 receptors has also been reported to be weaker in tumor tissues than in normal tissues. Indeed, EP4 receptors have been suggested to play a role in the maintenance of colorectal homeostasis. This study aimed to examine the underlying mechanisms/reasons for why inconsistent findings have been reported regarding EP4 receptor expression levels in homeostasis and carcinogenesis by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It was shown that HIF1α displaces MYC binding from the p21 promoter and upregulates the expression of p21 (Koshiji et al, 2004). HIF1α also competes against MYC for binding to SP1, a known coactivator of MYC, at the promoters of MYC target genes, such as MSH2, MSH6, and NBS1, which encode DNA repair proteins (Koshiji et al, 2005;To et al, 2006), and the recently reported E−type prostanoid (EP4) receptors (Seira et al, 2018). Third, several studies showed that HIF promotes proteasomal degradation of MYC under chronic hypoxia condition (Zhang et al, 2007;Wong et al, 2013).…”
Section: The Regulation Of Myc By Hifmentioning
confidence: 99%
“…It was shown that HIF1α displaces MYC binding from the p21 promoter and upregulates the expression of p21 (Koshiji et al, 2004). HIF1α also competes against MYC for binding to SP1, a known coactivator of MYC, at the promoters of MYC target genes, such as MSH2, MSH6, and NBS1, which encode DNA repair proteins (Koshiji et al, 2005;To et al, 2006), and the recently reported E−type prostanoid (EP4) receptors (Seira et al, 2018). Third, several studies showed that HIF promotes proteasomal degradation of MYC under chronic hypoxia condition (Zhang et al, 2007;Wong et al, 2013).…”
Section: The Regulation Of Myc By Hifmentioning
confidence: 99%
“…Kambe et al reported that specificity protein 1 (Sp-1) binds to the region −197 to −160 of the EP4 promoter to promote its expression ( 30 ). EP4 expression is enhanced by c-Myc, which binds to Sp-1 under low cellular density conditions, but is downregulated under high cellular density conditions via HIF-1α, which may prevent c-Myc and Sp-1 from DNA-binding in normal colorectal epithelial cells ( 31 ). Oh et al found that human papillomavirus E5 protein induces EP4 expression in cAMP response element (CRE)-dependent pathway in cervical cancer cells, which is inhibited by an EP4 antagonist, inhibitor of cAMP-dependent protein kinase or phosphatidylinositol 3-kinase, and CRE decoy ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, HIF1A displaces MYC binding from the promoter of cyclin-dependent kinase inhibitor 1A (CDKN1A, p21cip1) and upregulates the expression of p21 (CDKN1A) in human HCT116 colorectal carcinoma cell line [106]. HIF1A also competes against MYC for binding to SP1, a coactivator of MYC, at the promoters of MYC target genes such as MutS homolog 2 (MSH2), MSH6, and nibirin, which encode DNA repair proteins, in human HCT116 colorectal carcinoma cell line [107,108] and the E-type prostanoid receptor in human HCA-7 colon cancer cell line [109]. Third, several studies have shown that HIF-1A promotes proteasomal degradation of MYC under chronic hypoxia conditions [104,[110][111][112].…”
Section: Effects Of Hif-1 Compared To the Effects Of Sp1 On Myc Gene ...mentioning
confidence: 99%